Renal fibrosis - Min Hyun Cho (Korean Pediatric Society, 2010)
Renal fibrosis, characterized by tubulointerstitial fibrosis and glomerulosclerosis, is the final manifestation of chronic kidney disease. Renal fibrosis is characterized by an excessive accumulation and deposition of extracellular matrix components. This pathologic result usually originates from both underlying complicated cellular activities such as epithelial-to-mesenchymal transition, fibroblast activation, monocyte/macrophage infiltration, and cellular apoptosis and the activation of signaling molecules such as transforming growth factor beta and angiotensin II. However, because the pathogenesis of renal fibrosis is extremely complicated and our knowledge regarding this condition is still limited, further studies are needed.